Human amniotic epithelial cells (HAECS); a potential cell type for the hepatic disorders - Qurat Ul Ain Khan,; Shumaila Usman,; Kanwal Haneef,; Bushra Wasim Khan,; Talat Mirza, (Journal of the Pakistan Medical Association, 2024)
Objective: To isolate a homogenous population of human amniotic epithelial cells (hAECs) from the amniotic membrane of the human placenta and differentiate them into hepatic-like cells with the help of small molecules. Method: hAECs were isolated by using the enzymatic digestion method and characterized for the presence of specific stem cell markers. In-vitro, hepatic differentiation of hAECs was carried out by using a combination of small molecules. Differentiated cells were observed under a live cell imaging microscope for morphological changes followed by gene and protein expression analysis by qPCR and immunocytochemistry respectively. Results: The isolated hAECs attained characteristic cuboid epithelial shape and express stem cells marker. The hepatic differentiation method was optimized based on soluble chemical compounds supplied in the culture medium. The differentiated hAECs phenotypically acquire hepatic-like cell features and expressed hepatic markers as well as hepatic protein albumin at immature levels. Conclusion: The isolated population of hAECs is highly proliferative. Moreover, hepatic markers expression in the isolated hAECs makes them an exclusive source for the treatment of chronic liver diseases. Keywords: Amnion, Immunohistochemistry, Epithelial, Albumins, Liver, Digestion, Placenta